Analysis Of Occupational Safety and Health in Islamic Worldview - Romzy Sulthanmalonga; Malik Sakhi Sultan Awan; M. Shohibul Mujtaba (Indonesian Journal of Islamization Studies, 2024)
Occupational safety and health or OSH are all activities to guarantee and protect the safety and health of workers through efforts to prevent work accidents and work-related diseases. If viewed from an Islamic point of view, OSH is very relevant to Islamic teachings, where OSH with the aim of its work is to prosper the Islamic world itself is a religion as well as a way of life, or even a civilization. In it are all the values and rules needed by every human being at all times. The research objective is to analyze Occupational Safety and Health in an Islamic worldview. The method used in this research is the library research method, namely research that refers to written sources or refers to literature related to the OSH research theme in an Islamic Worldview perspective. the result of the research is that OSH has the principles of an Islamic worldview, namely, OSH as a form of human endeavor to anticipate an accident, of course based on an understanding of reality. Meanwhile, the ISLAMIC WORLDVIEW as a point of view based on Islamic values, so that all one's actions will reflect Islamic values.